2023
DOI: 10.1007/s10389-023-01964-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smartphone use at bedtime on sleep quality and academic activities among medical students at Al -Azhar University at Cairo

Abstract: Aim Smartphone use has become prevalent and rapidly expanding. Therefore, it is essential to determine the potential adverse effects. This study aims to assess the prevalence of smartphone use at bedtime and its association with sleep quality and educational-related activities among medical students. Subject and methods The current cross-sectional study included 1184 male and female undergraduate medical students at Al-Azhar University in Cairo. We used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The first [17,18]. Furthermore, the table's results reveal that excessive smartphone users have significantly higher insomnia scores than their non-excessive peers (11.015 vs. 9.272) [19]. This indicates a correlation between excessive smartphone use and insomnia, consistent with previous research on the adverse effects of excessive smartphone use on adolescents' sleep [20].…”
Section: Relationship Between Excessive Smartphone Use and Insomniasupporting
confidence: 84%
“…The first [17,18]. Furthermore, the table's results reveal that excessive smartphone users have significantly higher insomnia scores than their non-excessive peers (11.015 vs. 9.272) [19]. This indicates a correlation between excessive smartphone use and insomnia, consistent with previous research on the adverse effects of excessive smartphone use on adolescents' sleep [20].…”
Section: Relationship Between Excessive Smartphone Use and Insomniasupporting
confidence: 84%
“…The suppression of melatonin secretion reduces sleep pressure and reinforces the propensity to stay awake ( 11 ). It has been demonstrated that, among university students, smartphone users at bedtime had a significantly higher prevalence of increased sleep latency in comparison to non-users ( 43 ). Hence, it could be argued that the tendency to delay bedtime that emerged with the present study might happen as a maladaptive coping mechanism that soothes stress and emotional overwhelming: using the smartphone before bed significantly contributes to individuals feeling satisfied and relaxed, further reducing sleep efficiency and increasing sleep latency ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The way students use their smartphones at bedtime is a growing concern and with good reason. Research by Elsheikh et al (2023) reveals that bedtime phone use is shockingly common among medical students, and it comes at a cost [12]. Students who cannot put their phones down struggle to fall asleep, stay asleep, and get enough sleep overall.…”
Section: Ratan Et Al's (2022) Investigation Of Smartphone Addictionmentioning
confidence: 99%
“…While home use indicates a desire for privacy and focus, the widespread practice of using phones in bed is alarming. Research clearly links this behavior to sleep disruption [12], highlighting a potential health concern for this student population.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation